TECHNOLOGICAL GAP ANALYSIS IN CHILLI PRODUCTION TECHNOLOGY IN PRAKASAM DISTRICT OF ANDHRA PRADESH - G.V. SUNEEL KUMAR, O. SARADA and (The Journal of Research, PJTSAU, 2019)
An ex-post-facto research design was used to analyze technological gaps in chilli production technology in Prakasam district of Andhra Pradesh during the year 2015-16. One hundred and fifty farmers from ten villages of five major chilli growing mandals represented the sample. Half of the farmers had medium technological gap followed by high and low gap. High technological gap was observed in the K fertilizer management (57.40%), manures use (55.11%), time of transplanting (54.46%), P fertilizer management (54.30), micronutrient management (51.80%), N fertilizer management (48.22%) and pest and disease management (46.67%). Education, farming experience, mass media exposure, innovativeness, economic motivation, extension participation and trainings undergone were negatively correlated with technological gap significantly at 0.01 level. The major constraints expressed by the chilli farmers were low market price, high incidence of thrips (92.00%), labour shortage (90.00%), increased cost of cultivation (87.33%), poor marketing facilities (80.00%), mixing of 2-3 insecticides in a single spray (78.67%), poor seed quality, insufficient irrigation facilities (76.00%), severe virus incidence (74.66%) and micro nutrient deficiencies (72.00%). More than half of the chilli farmers felt non availability of commercial nursery in the village (66.00%), colour patches on capsules with sprinkler irrigation (61.33%), spodoptera and midge problem (55.33%) and incidence of dieback and root rot (53.33%) were the constraints in chilli cultivation